Political Correctness, Social Image, and Information Transmission - Braghieri, Luca (American Economic Review, 2024)
A prominent argument in the political correctness debate is that people feel pressure to publicly espouse sociopolitical views they do not privately hold, and that such misrepresentations might render public discourse less vibrant and informative. This paper formalizes the argument in terms of social image and evaluates it experimentally in the context of college campuses. The results show that (i) social image concerns drive a wedge between the sensitive sociopolitical attitudes that college students report in private and in public; (ii) public utterances are indeed less informative than private utterances; and (iii) information loss is exacerbated by (partial) audience naïveté. (JEL D72, D83, D91, I23, Z13)